Auditoría de calidad a la cooperativa de ahorro y crédito Cacpeco matriz ubicada en la ciudad de Latacunga provincia de Cotopaxi en el periodo del 01 de enero al 31 de diciembre 2013 - Chasiquiza Casillas, Mayra Alejandra (2015)
The work of Cooperative Savings and Credit Research perform to CACPECO, in Latacunga city, which is an entity that enjoys of a well accepted financial solvency despite this it has some shortcomings respect to the quality of service that is offered by staff of the Institution. It is one variable demonstrating inportance‘s achieve customer satisfaction through Service received by the area of Cooperative CACPECO human talent, this project has as a aim to research the quality of the service and analyze performance with which the staff handled the examination was directed to was directed to evaluation costumers these were efficiency, and effectivines to the service, However was determined that is necessary to work more regarding, the policies manual to stablish and improve costumers Culture Client….